Fragmented Fat Transfer for Massive Weight Loss Gluteal Contouring - Mendes, Flavio Henrique [UNESP]; Viterbo, Fausto [UNESP] (Wolters Kluwer, 2022)
SUMMARY: A recently introduced novel fragmentation technique has made it possible to convert fat tissue from apronectomy into large-scale viable lipograft, providing a glimpse of an alternative to traditional liposuction and its harvesting limitations. The purpose of this study was to assess the initial clinical evidence on fragmented fat transfer to restore volume and enhance deflated gluteal contours in a sample of massive weight loss patients. The authors retrospectively reviewed medical records of 20 women who received autologous buttock fat grafts that were harvested and fragmented following belt lipectomies and/or fleur-de-lis abdominoplasties. The average total volume subcutaneously grafted into the buttocks was 720 ml (bilateral), ranging from 500 ml to 960 ml. No local gluteal complications, such as seroma, infection, fat necrosis, or subcutaneous nodulations, were reported. Photographic observation of postoperative results over a 6- to 14-month follow-up period showed clear enhancement of body contouring in all patients, especially in those in whom fat transfer was combined with circumferential lifts. Fat fragmentation has proved useful and effective in providing great amounts of viable fat graft in a safe, simple, and reproducible technique without noticeable complications. The method eliminates the organic response to the insult of liposuction while using the entirety of formerly discarded apronectomy tissue to provide fine, transferable, autologous fat without increasing operative time. Although preliminary, the authors' clinical findings with this new technique support further studies of fragmented fat as an alternative to liposuction in gluteal fat grafting. Additional potential applications, including in wound healing and regenerative medicine, are worth exploring. . CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.